2022
DOI: 10.1097/mol.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nonalcoholic steatohepatitis-associated cardiomyopathy: key roles for liver–heart crosstalk

Abstract: Purpose of reviewNonalcoholic steatohepatitis (NASH) is a multisystem disease that affects not only the liver but also heart, pancreas, and kidney. We currently lack a comprehensive understanding of mechanisms responsible for the development of NASH-associated cardiomyopathy or the influence of sex on pathophysiology. There is a critical need to address these gaps in knowledge in order to accelerate translation of knowledge into clinical practice. Recent findingsNASH and cardiovascular disease share common ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It has been shown that conventional dendritic cells produce The increase in plasma Cer(42:1), a long-fatty acid containing ceramide (d18:1/24:0), may contribute to potentiate lipotoxicity in muscle (51) but it did not experience changes in the liver. Although, in the present design, this was not translated into development of metabolic syndrome, some authors have raised this possibility (52,53). The increase in the absolute level of an individual NEFA (FA 16:0) without changes in total NEFA levels in pig point out that individual species of FA are more sensitive parameters of metabolic changes that total NEFA levels.…”
Section: Prolonged Consumption Of the Steatotic Diet By Pigs Resulted...mentioning
confidence: 62%
“…It has been shown that conventional dendritic cells produce The increase in plasma Cer(42:1), a long-fatty acid containing ceramide (d18:1/24:0), may contribute to potentiate lipotoxicity in muscle (51) but it did not experience changes in the liver. Although, in the present design, this was not translated into development of metabolic syndrome, some authors have raised this possibility (52,53). The increase in the absolute level of an individual NEFA (FA 16:0) without changes in total NEFA levels in pig point out that individual species of FA are more sensitive parameters of metabolic changes that total NEFA levels.…”
Section: Prolonged Consumption Of the Steatotic Diet By Pigs Resulted...mentioning
confidence: 62%
“…This dysregulation perhaps extends beyond hepatic boundaries, affecting systemic metabolic processes such as glucose uptake, glycogen synthesis, glucose and fat oxidation, lipid storage, and lipolysis. Ectopic fat deposition with increased inflammation resulting from MASLD and obesity in non-AT, pose a substantial risk factor for CVDs, highlighting the severe pathogenic impact of MASH beyond the liver ( Ferrara et al, 2019 ; Njoku et al, 2022 ). Defects in hepatic lipid metabolism not only precipitate intrahepatic lipid accumulation but also promotes lipid storage in non-hepatic tissues, highlighting the liver’s central role in systemic lipid homeostasis.…”
Section: Liver Complications Of Masld/mashmentioning
confidence: 99%
“…However, it is likely that systemic inflammation and spill over mechanisms play a role in promoting inflammation in other tissues. Central to the systemic nature of MASH is the concept of hepatic inflammatory “spill over,” where pro-inflammatory mediators produced in the liver ( Njoku et al, 2022 ), as a consequence of lipid accumulation and cell injury (lipotoxicity), disseminate through the bloodstream to distant organs ( Buzzetti et al, 2016 ; Loomba et al, 2021 ; Zhong et al, 2024 ). This process is facilitated by an array of cytokines, chemokines, and other inflammatory molecules, such as TNF-α, interleukins (e.g., IL-6, IL-1β), and C-reactive protein (CRP), which are elevated in the context of MASH ( Buzzetti et al, 2016 ; Machado and Diehl, 2016 ; Mitten and Baffy, 2022 ).…”
Section: Liver Complications Of Masld/mashmentioning
confidence: 99%
See 2 more Smart Citations